Corrosion Protection of Carbon Steel Using Expired Drugin Acidic Mediu: Review - Ali, Enas H.; Farook, Azhar; Ahmed, Zainab W. (American Journal of Biomedicine and Pharmacy, 2026)
When it comes to corrosion, there is no easy solution. The structure and features for a metal surface and a surrounding environment change as a result of the corrosion process. Inhibitors like organic and inorganic ones were proven to be costly and hazardous while also having significant environmental consequences. As a result, these inhibitors can only be used sparingly in the fight against corrosion. As corrosion inhibitors, pharmaceuticals have been studied in the past. Using nontoxic, affordable, and environmentally benign medicines as corrosion inhibitors was discovered. As corrosion inhibitors for diverse metals such as mild steel, carbon steel, and aluminum steel have been studied in several studies employing various medications (melatonin, cephapirin, Orlistat and tramadol among others). Studies have shown that these medicines’ inhibitory action forms an insoluble compound on the metal surface, protecting it against corrosion. To determine the effectiveness of various drugs in inhibiting corrosion, researchers used various methodologies, including the weight loss technique (WL), measurements of potentiodynamic polarizations (PDPs), electrochemical frequency modulation (EFM) besides electrochemical impedance spectroscopy (EIS). X-Ray Diffraction, Scanning Electron Microscopy besides Atomic Force Microscopy were adopted to study a surface morphology for metals before and after medicines were added.